Réponses

2013-02-16T16:30:35+01:00

 

A = 3 + 1/(7+1/6)

    = 3 + 1/(43/6)

    = 3 + 6/43

    = 129/43 + 6/43

    = 135/43

    = 3,14

 

 

1) 

   (2x+3)(5-x) - (2x+3)^2

= 10x-2x^2+15-3x - (4x^2+12x+9)

= -6x^2 -5x + 6

 

 2)

  (2x+3)(5-x) - (2x+3)^2

= (2x+3)((5-x)-(2x+3))

= (2x+3)(2-3x)

 

3)

Un produit est nul si et seulement si au moins l'un de ses facteurs est nul :

        (2x+3)(2-3x) = 0

<=> (2x+3) = 0 ou (2-3x) = 0

<=> 2x = -3 ou -3x = -2

<=> x = -3/2 ou x = 2/3

 

4) Pour x = 3, on a :

F(3) = -6*3^2 - 5*3 + 6

        = -54-15+6

        = -63

 

Sauf erreur de ma part.